INTEGRATION OF ISLAMIC VALUES AND THERAPEUTIC COMMUNICATION TECHNIQUES IN GROUP COUNSELLING: Case Study of MTs. Nurul Iman, Bandung City - Sakinah Widyaningrum; Siti Nurjanah Fatonah (AL-TAZKIAH, 2025)
This study examines group counselling practices at MTs Nurul Iman in Bandung City to understand how guidance and counselling teachers apply the principles of empathy, active listening, and spiritual approaches in building therapeutic relationships with students. Theoretically, this research enriches the scientific treasury of Islamic guidance and counselling by developing a conceptual model of therapeutic communication based on spiritual values. Practically, the research results indicate that therapeutic communication in madrasah group counselling still needs strengthening to be applied more consistently and integrated into the practice of guidance and counselling services. Therefore, this research is expected to enhance the professional awareness of madrasa guidance and counselling teachers regarding the importance of therapeutic communication as the foundation of the counselling relationship, and to encourage the application of more humane, religious, and contextual communication strategies in supporting the psychological and Islamic moral development of students. Data collection was done through in-depth interviews, observation, and documentation. The research findings indicate that the group counselling process unfolds through three main stages: problem identification, implementation of counselling, and evaluation of service. At each stage, the counselor optimizes therapeutic communication skills as the primary instrument of service, which includes creating a conducive atmosphere to build the client's sense of safety and openness, applying active listening to deepen understanding of the client's experiences, using Islamic communication techniques to strengthen meaning and spiritual motivation, and building a relationship of mutual trust as the foundation for the effectiveness of the group counseling process in Islamic guidance and counselling.